2007
DOI: 10.1002/hep.21898
|View full text |Cite
|
Sign up to set email alerts
|

Distinct hepatitis C virus core and F protein quasispecies in tumoral and nontumoral hepatocytes isolated via microdissection

Abstract: Hepatitis C virus (HCV) genetic variability may be involved in liver carcinogenesis. We investigated HCV core and corresponding putative F protein genetic variability in hepatocellular carcinoma (HCC) and cirrhotic nodules. Hepatocyte clusters from 7 patients with HCC and HCV1b-related cirrhosis were isolated via microdissection of HCC tissues and 2 nontumoral cirrhotic nodules. The HCV core complementary DNA was cloned and sequenced from each liver compartment and from the serum of 2 patients. Nucleotide dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 49 publications
5
44
0
1
Order By: Relevance
“…Our data also show that the differences in quasispecies distribution are not the result of differences in host selective pressure in malignant hepatocytes, as was suggested previously (20). The molecular mechanisms leading to high viral diversity within the tumor despite the significant drop in viral replication remain to be elucidated.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our data also show that the differences in quasispecies distribution are not the result of differences in host selective pressure in malignant hepatocytes, as was suggested previously (20). The molecular mechanisms leading to high viral diversity within the tumor despite the significant drop in viral replication remain to be elucidated.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with this hypothesis, Mantel test analysis demonstrated significant differences in HCV quasispecies distribution between the tumorous and nontumorous compartments, providing evidence of HCV compartmentalization between these two liver areas. In contrast, analysis of multiple liver areas in the control patients with non-HCC cirrhosis demonstrated no evidence of HCV compartmentalization within the liver or between the liver and serum, further indicating that the presence of HCV compartmentalization is unique to tumor-containing livers (20,41). Interestingly, viral compartmentalization between plasma and extrahepatic sites, including leukocytes (42), PBMCs (43), and the brain (44), also has been reported in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies have shown that HCV compartmentalizes within the host, with quasispecies compositions differing between different organs (10,11). The primary target of HCV is the liver, where it forms distinct foci of infection (12), but it also infects extrahepatic sites, including the brain (10,11).…”
mentioning
confidence: 99%